Zoom in, zoom out: Geographic scale and multinational activity - Mudambi, Ram; Li, Lee; Ma, Xufei; Makino, Shige; Qian, Gongming; Boschma, Ron (Journal of International Business Studies, 2018)
IB scholars have long studied the multinational enterprise (MNE) and now recognize that its ability to capture value stems from its control of bottleneck assets. In contrast, economic geographers and regional scientists have largely focused their attention on the locations within which economic and business systems operate. In this article, we draw on both these literatures. We emphasize that the MNE’s integration of upstream and downstream strategic considerations to maximize its control of bottleneck assets implies an optimal geographic footprint. This optimal footprint is typically asymmetric, with a spatial scale that varies dramatically across the different activities of the value chain. Upstream innovation processes are likely to be based on highly local considerations like the availability of specialized resources and collocation advantages. In contrast, downstream sales and marketing processes are likely to driven by imperatives of high volume and global reach. Further, in the current fast clockspeed business environment, the location and nature of bottleneck assets are likely to change rapidly and unpredictably, making organizational flexibility a crucial MNE capability.